Adaptation to globalization in renewable energy sources: Environmental implications of financial development and human capital in China - Ashraf, Muhammad Saeed; Mingxing, Li; Zhiqiang, Ma; Ashraf, Rana Umair; Usman, Muhammad; Khan, Irfan (Frontiers in Environmental Science, 2023)
This research article examines the dynamic impact of globalization, environmental quality, and financial development on renewable energy in China. Promoting renewable energy is crucial for solving global environmental problems. In China’s case, no such studies investigate the role of renewable energy as a dependent variable in globalization, financial development, and environmental quality. To check cointegration and long-run/short-run dynamics, this study uses Autoregressive Distributed Lag (ARDL) model, which can predict the actual positive and negative change in the independent variables and their effects on the dependent variable. We also used the Johansen cointegration technique to verify the results of bound testing. The results suggest significant long-run and short-run relationships among the study variables. Furthermore, the causality analysis reveals a bidirectional relationship between renewable energy with globalization, financial development, environmental quality, human capital, and economic growth in the long run. In the short run, renewable energy Granger significantly causes economic growth and carbon emissions.